Hadith #3044 - Sahih al-Bukhari - Auf bin Malik al-Ashja'i (Sahih al-Bukhari)
I went to the Prophet (ﷺ) during the Ghazwa of Tabuk while he was sitting in a leather tent. He said, “Count six signs that indicate the approach of the Hour: my death, the conquest of Jerusalem, a plague that will afflict you (and kill you in great numbers) as the plague that afflicts sheep, the increase of wealth to such an extent that even if one is given one hundred Dinars, he will not be satisfied; then an affliction which no Arab house will escape, and then a truce between you and Bani
Grade: Sahih